Examining visitors’ event experiences at festivals and special events: Proposed framework. - Norazirah, Ayob; Nabsiah, Abd. Wahid; Azizah, Omar (2010)
Festivals and special event has becoming an important feature in a tourist destination’s general tourism development and marketing plan. Many have realized the important benefits of staging festivals and special events. Nonetheless, events require special consideration conceptualizing and understanding the event outcome based on experiential perspective. Only from the experiential view, the event researchers and organizer are able to grab the holistic view of event outcome created by a festival or special event. Hence, this study attempts to take a step towards an improved understanding and examination on the broader picture created by the festivals and special events by considering the experiential approach. Moreover, the framework strives to not only focusing on the physical products and services but also take account of emotional and value aspects, and affects of social interactions which might be very important aspects in a celebration of a festival or special event. The primary objective of this paper is to present a conceptual framework based on experiential paradigm that able to systematically assess visitors’ personal event experiences in context of festival or special event. Specifically, the framework enables examination of relationships of several important variables in event settings namely, event features, social interactions, visitor’s event experience, visitor’s overall satisfaction, future intentions, and level of experience.